In vitro evaluation of the production of reactive oxygen species in silver metallophosphazenes - Gil López, Ana; Batanero Mantero, Ana; Maisanaba Hernández, Sara; Llana-Ruiz Cabello, María; Jiménez Villar, Josefina; Repetto Khun, Guillermo (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2021)
Motivation: Phosphazenes (FZ) are polymers that have been shown to have a high therapeutic potential in recent years (Andrianov and Allcock, 2018). Among its derivatives, metalphosphazenes should be highlighted due to the interest in the biological activity of metal complexes (Gascón et al., 2020). Likewise, the estimation of the toxic risk of a substance is a complex process in which the risks and benefits for organisms or populations are related (Reppeto y Repetto 2009). In vitro models of the cell culture type allow studying the toxicity of xenobiotics at the systemic, cellular and molecular level (Meseguer, 2016). Methods: In the present work, the oxidative stress induction of two silver-FZ complexes was evaluated by studying the generation of reactive oxygen species (ROS) (Meseguer, 2016) in the MCF-7 cell line. The intracellular formation of ROS was determined fluorimetrically with the reagent 2´, 7´-dichlorodifluorescein 3´, 6´-diacetate (Hempel et al., 1999); using tert-butyl hydroperoxide and hydrogen peroxide as positive controls. The concentrations used were the EC50 and its sub-concentrations, being for compound 1: 2.34 µM, 1.17 µM and 0.585 µM; and for compound 2, 1.60 µM, 0.80 µM and 0.40 µM. These concentrations were determined using the alamar blue and neutral red cytotoxicity tests. ROS production was measured every 30 min, from time 0 to 120 min. Statitical significance between concentrations and the control was determined by Dunnett´s Multiple Comparison Test, using GraphPad Software. Results: Compound 1 showed the disappearance of ROS observed (t = 0 min p <0.01) throughout the test time, observing non-significant differences with respect to the control at the end of the same (t = 120 min). However, compound 2 maintained a statistically significant difference throughout the experiment for all concentrations, except for the maximum concentration tested (1.60 µM), which shows a decrease at the end time (t = 120 min). Conclusions: In view of the results obtained, it is observed that the cells exposed to compound 1 seem to recover over time from the initial induction of ROS. Compound 2 induces ROS in MCF-7 cells. This difference in behavior could be related to the different proportion of silver present in both compounds, of one and two molecules, respectively. It is necessary to carry out a more exhaustive evaluation of the oxidative profile of these compounds, in order to determine if antioxidant defense mechanisms could be active.